Design and Visual Thinking Model for Thai Undergraduate Student Online Creative Thinking and Creative Products Promotion - Natnicha Khongprakob, Thiyaporn Kantathanawat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The design thinking (DT) process is a thought process to solve problems and develop new ideas to find solutions that focus on a user-centered perspective. Visual Thinking (VT) is the beginning of visualization of a story that leads to an understanding of complex problems. Moreover, many scholars agree that DT and VT are tightly joined in educational learning management. Therefore, to nurture students' creativity and continuous development that can be used as a base for creating creative future products in the future, we developed a design and visual thinking model (DVTM). The DT process is combined with VT techniques to promote creativity and critical thinking. From the qualitative analysis, seven experts in various fields were selected to participate in a Connoisseurship Seminar. The content analysis made use of a five-level Likert type learning style suitability scale. The collected data were then analyzed by use of the mean and the standard deviation (S.D.). The final DVTM consisted of five steps including; Step 1) idea stimulation, Step 2) problem identification, Step 3) idea and visualization generation, Step 4) testing, and Step 5) presentation and sharing which were determined to be appropriate by the experts at a good level (mean = 4.46, S.D. = 0.41) This Digital Learning Platform (DLP) style should be applied in the activities of students at the undergraduate level.